SIMULTANEOUS SELECTION FOR EARLY-MATURITY AND HIGH SEED AND OIL YIELD IN ADVANCED SPRING CANOLA BREEDING LINES UNDER TERMINAL HEAT AND DROUGHT STRESS - Hossein Zeinalzadeh-Tabrizi (Journal of Animal and Plant Sciences, 2026)
Developing climate-resilient canola cultivars is crucial for improving oilseed productivity in drought-prone regions. The present study aimed to identify the early-maturing and high-yielding canola lines suitable for the Moghan region in Northwest Iran, addressing challenges like terminal heat and drought stress. The study assessed 21 canola genotypes, comprising 18 promising open-pollinated breeding lines and three commercial check cultivars (RGS003, Dalgan, and Hyola 4815), over two consecutive cropping seasons of 2018-2019 and 2019-2020. The multi-trait genotype-ideotype distance index (MGIDI) was used to evaluate the performance of 21 canola lines. During the growing seasons, the data were recorded on phenological, physiological, and productive traits. Results showed significant variation across genotypes, particularly in phenological traits like days to maturity (DMA) and structural traits such as plant height (PH) and stem diameter (SD). Overall, the three canola genotypes (G9, G12 and G13) exhibited early maturity and outperformed others by avoiding terminal heat and drought stress, and improvements were observed in SY (4.8%) and OY (6.2%). Furthermore, these three promising genotypes exhibited superior performance in seed and oil yields, revealing their considerable adaptability to terminal heat and drought stress and related agronomic traits. This study highlighted the efficiency of multivariate selection indices, such as the MGIDI, in significantly enhancing crop yield and stress tolerance.
Keywords: canola breeding; MGIDI; stress tolerance; seed yield; phenological